Freedom in organizations - Keeley, Michael (Journal of business ethics, 1987)
Organizations in competitive markets are often assumed to be voluntary associations, involving free exchange between various participants for mutual benefit. Just how voluntary or free organizational exchanges really are, however, is problematic. Even the criteria for determining whether specific transactions are free or coerced are not clear. In this paper, I review three general approaches to specifying such criteria: consequentialist, descriptive, and normative. I argue that the last is the most reasonable, that freedom is an essentially moral concept, whose meaning is relative to preconceptions of human rights. Implications for freedom of contract are discussed., [O]n the whole, market competition, when it is permitted to work, protects the consumer better than do the alternative government mechanisms that have been increasingly superimposed on the market. ... If one storekeeper offers you goods of lower quality or of higher price than another, you're not going to continue to patronize his store. If he buys goods to sell that don't serve your needs, you're not going to buy them. The merchants therefore search out all over the world the products that might meet your needs and might appeal to you. And they stand back of them because if they don't, they're going to go out of business. When you enter a store, no one forces you to buy. You are free to do so or go elsewhere. That is the basic difference between the market and a political agency. You are free to choose (Friedman and Friedman, 1979, 222–223)., The consumer's experience of modern commercial life is not one of freedom in the full sense posited by traditional contract law, but rather one of submission to organizational domination, leavened by the ability to choose the organization by which he will be dominated. ... Strong competition, far from ameliorating the situation, will only exacerbate it (Rakoff, 1983, 1227–1229).